(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effect of improving lumbar spinal nerve root compression and quality of life of high intensity LASER therapy combined with Doc hoat tang ky sinh pills and massage - accupressure in the treatment of patients with sciatica. Subject and methods: Control open clinical intervention with 60 patients, before and after treatment comparison, and comparison between study and control group. Results: Both groups of patients had improvements in nerve root compression after the study, with the study group tending to improve more than the control group. After 20 days of treatment, the average Laseguè angle index of the study group was 61.50 ± 5.89 degrees, that of the control group was 55.33 ± 7.06 degrees (p < 0.05); the average number of Valleix pain points in the control group was 0.97 ± 0.61 points, and that of the study group was 0.34 ± 0.55 points (p < 0.05). After 20 days of treatment, the QBPDS index of the control group and the treatment group both improved statistically, of which the study group had a greater improvement (p < 0.05). Conclusions: High intensity LASER therapy combines with Doc hoat tang ky sinh pill and massage - acupressure has the effect of improving lumbar spinal nerve root compression and quality of life in patients with sciatica.